Tales from Shakespeare - Lamb, Charles; Lamb, Mary (The Macmillan Company New York, 1958)
First published in 1807, (3z(BTales from Shakespeare(3y (Bis the classic retelling of Shakespeare$1 (Bs plays by brother and sister duo Charles and Mary Lamb. All told twenty of Shakespeare$1 (Bs plays are represented in this work. On what basis the two made their selection of tales is unknown, the English Histories are left unattempted, as well as the Roman Plays. Of the comedies only (3z(BLove$1 (Bs Labour$1 (Bs Lost(3y (Bis omitted. As Alfred Ainger comments in his introduction (3z(Bperhaps Miss Lamb felt how little would have remained of the original comedy when the poetical element in its language and the brilliant wit of its dialogue had been removed(3y(B. What is represented of Shakespeare$1 (Bs plays is a magnificent retelling of some of his most popular works, ideal for introducing young readers to the brilliance of the Bard. As the two write in their preface (3z(BThe following Tales are meant to be submitted to the young reader as an introduction to the study of Shakespeare,(3y (Bso (3z(Bthat the true Plays of Shakespeare may prove to them in older years$1 (Benrichers of the fancy, strengtheners of virtue, a withdrawing from all selfish and mercenary thoughts, a lesson of all sweet and honourable thoughts and actions(3y(B. This edition is printed on premium acid-free paper, includes an introduction by Alfred Ainger, and illustrations by Arthur Rackham.s
960L
Keywords: Shakespeare, William; Shakespear plays